Feminist Egalitarian Biblical Interpretation and the Christian Right - Winslow, Karen Strand (The Oxford handbook of feminist approaches to the Hebrew Bible, 2020)
The egalitarian interpretation of Scripture is based on the view that Scripture does not limit women’s roles and contributions in any arena, including the Church. Although egalitarians recognize that Scripture represents patriarchal interests, their interpretations highlight the positive depictions of women in the Bible. They claim that many women figures disrupt traditional interpretations of gender. This position contrasts to complementarian biblical interpretations that use the Bible to restrict women from ecclesial leadership, without attention to textual and historical contexts that mitigate universal application. Christian egalitarians also contribute to feminism’s concern about women’s global equality via social media campaigns, organizations, blogs, and scholarship. The essay discusses relevant examples to show that all of them focus on women’s experiences in church, biblical teaching, and Christian feminist identity.